2013
DOI: 10.1097/ta.0b013e318298b0a4
|View full text |Cite
|
Sign up to set email alerts
|

Seven deadly sins in trauma outcomes research

Abstract: Background Because randomized clinical trials (RCTs) in trauma outcomes research are expensive and complex, they have rarely been the basis for the clinical care of trauma patients. Most published findings are derived from retrospective and occasionally prospective observational studies that may be particularly susceptible to bias. The sources of bias include some common to other clinical domains, such as heterogeneous patient populations with competing and interdependent short- and long-term outcomes. Other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…The trial addressed most of the limitations found in previous randomized trauma resuscitation trials, including lack of blinded treatment assignment, enrollment after bleeding slowed, survival and selection biases, and small sample size. 48,5561 The trial was performed under exception from informed consent so that patients with severe bleeding could be enrolled rapidly and required that all blood products be immediately available for infusion within 10 minutes of calling the blood bank (Supplement 1). The selection criteria used in this study resulted in the rapid enrollment of patients who were severely bleeding, critically injured, in shock, and transfused with a median greater than 19 U of blood products.…”
Section: Discussionmentioning
confidence: 99%
“…The trial addressed most of the limitations found in previous randomized trauma resuscitation trials, including lack of blinded treatment assignment, enrollment after bleeding slowed, survival and selection biases, and small sample size. 48,5561 The trial was performed under exception from informed consent so that patients with severe bleeding could be enrolled rapidly and required that all blood products be immediately available for infusion within 10 minutes of calling the blood bank (Supplement 1). The selection criteria used in this study resulted in the rapid enrollment of patients who were severely bleeding, critically injured, in shock, and transfused with a median greater than 19 U of blood products.…”
Section: Discussionmentioning
confidence: 99%
“…Assigning patients at the opposite extremes of bleeding severity to the same 0-RBC subgroup reveals how the 24 hour RBC classification actually defeats the purpose of stratification, namely, to form more homogeneous patient subgroups. 1 …”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,30 Because randomization was expected to balance potential confounders across study arms, the data were stratified by MT to reveal HSD modifying effects, or whether the MT subgroup benefited more than the alternate subgroups (receiving 1–9 and 0 RBCs, respectively). 11,12 Despite favorable HSD effects in the MT subgroup, opposite effects in the 0-RBC subgroup halted the pivotal trial early.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While early transfusion of plasma and platelets has been associated with improved outcomes [2,46], findings among observational studies seeking to identify optimum trauma transfusion protocols have been conflicting and difficult to interpret [7,8]. In earlier works [9,10], our group has identified major challenges in the design and statistical analysis of trauma transfusion studies.…”
Section: Introductionmentioning
confidence: 99%